PENGEMBANGAN MEDIA TRUTH OR DARE BERBASIS BOARD GAME NATURE ADVENTURE PEMBELAJARAN IPAS PESERA DIDIK KELAS III SD NEGERI 7 KAMPUNGDALEM - Kurniawan, Rizky; Satria, Aditya Pringga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Low active engagement in learning is a challenge in the lower grades of primary school. Grade III students are still at the concrete thinking stage, so they are more interested in fun activities and are easily distracted by less interactive media or the use of devices such as gadgets. This research aims to development Truth or Dare learning media based on Board Game themed Nature Adventure on the material of natural appearance using the developer model applied using the Teams Games Tournament (TGT) approach which emphasizes group cooperation, healthy competition, and active involvement of students through a fun and not boring learning atmosphere. The results of validation carried out by media, material, and language experts, showed that the media obtained a validity score of 90.5% for media, 96% for material, and 94% for language, all of which were in the very valid category. The applicability test was conducted through a questionnaire distributed to teachers and third grade students at SD Negeri 7 Kampungdalem. The results showed an applicability of 98.1% from teachers and an average of 92.1% from students. The results of the field trial prove that this media is able to increase the enthusiasm, motivation, and active involvement of students during learning in the classroom.